OP13 Evaluating experiences of advance care planning facilitators: results from the international ACTION study. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Christensen, CA; Adsersen, M; Johnsen, AT; Seymour, J; Bulli, F; Cerv, B; Deliens, L; Van der Heide, A; Korfage, I; Lunder, U; Pollock, K; Preston, NJ; et al.
Abstract : Background: The ACTION trial evaluates the effect of the ACTION Respecting Choices (RC) advance care planning (ACP) intervention in patients with advanced cancer in six European countries. Systematic evaluations of such ACP conversations by facilitators are currently lacking. We developed and applied a 10-item facilitator-reported instrument. Methods: The instrument asked about the facilitator's perception of the patient's and the personal representative's (PR) reactions to and engagement with the intervention and satisfaction with the intervention. Results: From March 2016 until February 2018, 272 conversations took place. Of these, 265 were evaluated. According to the facilitators, 32% of the patients did not appear to understand all questions asked (29% understood most, 3% understood about half), and 36% were not able to answer all questions (31% answered most, 4% answered about half, 1% answered fewer). Furthermore, 38% of the patients and 27% of the PRs did not appear to perceive all questions as OK (patients: 33% perceived most as OK, 3% about half, 2% fewer; PR: 24% most, 3% about half). Facilitator perception of patient satisfaction, PR satisfaction and their own satisfaction with ACP conversations ranged 40–54% for 'very much', 41–49% for 'quite a bit' and 5–11% for 'a little'. Conclusion: To our knowledge, this is the first clinical trial to systematically evaluate the feasibility of ACP conversations from the facilitator perspective. Parts of the ACP intervention appeared to be challenging for patients and PRs. These results, together with qualitative data, will help understand the outcomes of the ACTION trial. Funding: EU's FP7.